International Conference on Advancements of Medicine and Health Care through Technology; 23 - 26 September 2009 Cluj-Napoca, Romania - Vlad, Simona; Ciupa, Radu V.; Nicu, Anca I. (IFMBE Proceedings,, 2009)
This volume presents the contributions of the second International Conference on Advancements of Medicine and Health Care through Technology (Meditech), held in September 2009 in Cluj-Napoka, Romania. The papers of this Proceedings volume present new developments in Health Care Technology, Medical Devices, Measurement and Instrumentation, Medical Imaging, Image and Signal Processing, Modelling and Simulation, Molecular Bioengineering, Biomechanics.